Increased antioxidative enzyme activity mediates the phytoaccumulation potential of Pb in four agroforestry tree species: a case study under municipal and industrial wastewater irrigation. Issue 7 (7th June 2021) - Hussain, Zafar; Rasheed, Fahad; Tanvir, Muhammad Ayyoub; Zafar, Zikria; Rafay, Muhammad; Mohsin, Muhammad; Pulkkinen, Pertti; Ruffner, Charles
Abstract: Wastewater used as irrigation water is causing heavy metal accumulation in the agro-ecosystems. A greenhouse study was conducted to compare the phytoaccumulation ability of four agroforestry tree species under different wastewater treatments. Three-month-old potted seedlings of Morus alba, Acacia nilotica, Acacia ampliceps, and Azadirachta indica were irrigation with tap water (C), municipal wastewater (MWW), and industrial wastewater (IWW). Results showed that MWW had a positive and IWW had a negative impact on biomass production in all the species. Acacia ampliceps showed the highest increment (65%) and showed the lowest decrease (5%) in total biomass under both MWW and IWW treatment. Pb concentration was also found highest in the leaves, stem and roots of Azadirachta indica (108.5, 46.2, 180.5 mg kg −1, respectively) under IWW. Production of H2 O2 was highest in IWW treatment with almost 148% increase observed in Azadirachta indica . Similarly, the production of antioxidative enzymes (Superoxide dismutase, Catalase and Peroxidase) was also highest in Azadirachta indica under IWW. Therefore, results suggest that along with high increment in total biomass, both Acacia ampliceps and Azadirachta indica showed high Pb concentration and an effective antioxidative defense mechanism and thus, can be used for planting in soils irrigated with MWW and IWW.